Recent advances of heterogeneously integrated III–V laser on Si. (October 2019) - Guo, Xuhan; He, An; Su, Yikai
Abstract: Due to the indirect bandgap nature, the widely used silicon CMOS is very inefficient at light emitting. The integration of silicon lasers is deemed as the 'Mount Everest' for the full take-up of Si photonics. The major challenge has been the materials dissimilarity caused impaired device performance. We present a brief overview of the recent advances of integrated III–V laser on Si. We will then focus on the heterogeneous direct/adhesive bonding enabling methods and associated light coupling structures. A selected review of recent representative novel heterogeneously integrated Si lasers for emerging applications like spectroscopy, sensing, metrology and microwave photonics will be presented, including DFB laser array, ultra-dense comb lasers and nanolasers. Finally, the challenges and opportunities of heterogeneous integration approach are discussed.